Pengaruh Komunikasi Pemasaran dan Media Sosial Instagram terhadap Keputusan Menggunakan Jasa DiiStudio - Lestari, Dian; Alfirahmi; Alifah, Ria (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
The growth of the photography industry has prompted DiiStudio to expand its business by offering innovative services in photography. To attract customers, DiiStudio has implemented various marketing strategies and leveraged social media platforms. This study aimed to examine the influence of marketing communication strategies and Instagram social media on the decision to use DiiStudio's services in Bekasi City. Employing a quantitative approach, the research involved 100 respondents as the sample. The results of the partial regression coefficient analysis showed a t-value of 6.092 for the marketing communication strategy variable and 6.388 for the Instagram social media variable, both exceeding the critical t-value of 1.984. These findings indicated that each independent variable significantly affects the dependent variable. Moreover, the F-test results show an F-value of 241.330, which is greater than the critical F-value of 3.09, further confirming the model’s overall significance. The multivariate correlation coefficient test yielded a correlation value of 0.913, signifying a very strong relationship between the independent variables and the dependent variable. Thus, it can be concluded that both marketing communication strategies and Instagram social media significantly influence the decision to use DiiStudio’s services. Keywords : Communication; Marketing; Instagram; Decision; Photo Studio;